Online CBT and ELIP Effectiveness Against The Degree of Post Partum Blues in Madura Urban - Elly Dwi Masita; Adenia Dwi Ristanti (Universitas Muhammadiyah Sidoarjo, 2021)
A preliminary study in February 2020 in northern Surabaya explained that 81% of post partum mothers experienced post partum blues. This condition has an impact on increasing the morbidity and mortality rates for mothers and newborns. This research to aim to know differencess between the CBT and ELIP methods on the degree of post partum blues in the urban Madurese in Surabaya. Type of research is quantitative with a non equivalent control group with desaign experimental approach. The population was 80 postpartum mothers. Sampling used a total sampling of 40 as pre and post CBT groups and 40 as pre and post ELIP groups. Instrument used EPDS through online screening, while CBT and ELIP were carried out through online web. Analysis test used pair t test and independent t test with p< 0.05. Result and implication has showing that are differences in the pre and post groups in each group of CBT of 22.87 and ELIP of 22.95, while independent t test has obtaine p = 0.81 it is mean that there is not differences in both CBT and ELIP to reducing the degree of post partum blues.